Executive functions and adaptive behaviour in individuals with Down syndrome. Issue 1 (9th November 2021) - Onnivello, S.; Colaianni, S.; Pulina, F.; Locatelli, C.; Marcolin, C.; Ramacieri, G.; Antonaros, F.; Vione, B.; Piovesan, A.; Lanfranchi, S.
Abstract: Background: Previous research has explored executive functions (EFs) and adaptive behaviour in children and adolescents with Down syndrome (DS), but there is a paucity of research on the relationship between the two in this population. This study aims to shed light on the profile of EFs and adaptive behaviour in DS, exploring the differences by age and investigating the relationship between these two domains. Method: Parents/caregivers of 100 individuals with DS from 3 to 16 years old participated in the study. The sample was divided into preschoolers (3–6.11 years old) and school‐age children (7–16 years old). Parents/caregivers completed either the Preschool Version of the Behaviour Rating Inventory of Executive Function (for children 2–6.11 years old) or the Second Edition of the same Inventory (for individuals 7 + years old). Adaptive behaviour was assessed with the Vineland Adaptive Behaviour Scale – Interview, Second Edition. Results: Findings suggest that individuals with DS have overall difficulties, but also patterns of strength and weakness in their EFs and adaptive behaviour. The preschool‐age and school‐age children's EF profiles differed slightly. While both age groups showed Emotional Control as a relative strength and Working Memory as a weakness, the school‐age group revealed further weaknesses in Shift and Plan/Organise . As concerns adaptive behaviour, the profiles were similar in the two age groups, with Socialisation as a strength, and Communication and Daily Living Skills as weaknesses, but with a tendency for preschoolers to obtain intermediate scores for the latter. When the relationship between EFs and adaptive behaviour was explored, Working Memory predicted Communication in the younger group, while in the older group the predictors varied, depending on the adaptive domains: Working Memory was a predictor of Communication, Inhibit of Daily Living Skills, and Inhibit and Shift of Socialisation . Conclusion: As well as elucidating the EF profiles and adaptive behaviour in individuals with DS by age, this study points to the role of EFs in adaptive functioning, providing important information for targeted interventions.